Symptomatic pulmonary embolus after catheter removal in children with catheter related thrombosis: A report from the CHAT Consortium. (19th October 2021) - Jaffray, Julie; Baumann Kreuziger, Lisa; Branchford, Brian; Wee, Choo Phei; Faustino, E. Vincent S.; Zakai, Neil A.; Croteau, Stacy E.; Silvey, Michael; Fargo, John H.; Cooper, James D.; Bakeer, Nihal; Stillings, Amy; et al.
Abstract: Background: Appropriate timing of central venous catheter (CVC) removal, in relation to start of anticoagulation, in children after the diagnosis of a CVC‐related thrombosis (CRT) is not well established. Objectives: This retrospective cohort study evaluated the incidence of symptomatic pulmonary embolism (PE) after CVC removal using data from the multi‐institutional Children's Hospital‐Acquired Thrombosis (CHAT) Consortium Registry. Patients/Methods: The CHAT Registry consists of data from children aged 0–21 years with a hospital‐acquired venous thromboembolism. Eligible subjects were those with CRT diagnosed <3 days after CVC removal. Subjects were excluded if the CRT was due to a failed CVC insertion. Subjects were divided into three groups: those with CVC removal without anticoagulation, those with CVC removal <48 h after starting anticoagulation, and those with CVC removal ≥48 h after starting anticoagulation. Results: A total of 687 CRT events from 663 subjects were included. A majority of CRT events were in subjects with peripherally inserted central catheters (62.3%, n = 428). For the 611 CRT events in which the CVC was removed, there was only one case of symptomatic PE (0.16%), which occurred <48 h after initiation of anticoagulation. Conclusions: While current guidelines suggest anticoagulation before CVC removal in the setting of a CRT to prevent embolization, CVC removal is not associated with symptomatic PE regardless of duration of anticoagulation before CVC removal.